Zygomatic Muscle Neurotization with Nerve Grafts and End-to-Side Neurorrhaphies: A New Technique for Facial Palsy - Viterbo, Fausto [UNESP]; Magnani, Lucas Vannuchi [UNESP]; Nunes, Helga Caputo (Wolters Kluwer, 2022)
Summary: Moebius syndrome is a rare congenital facial palsy that can generate serious emotional repercussions, mainly due to the inability to smile. Currently, no treatment is available; however, surgery can restore muscle function. This case report introduces a new technique for the treatment of Moebius syndrome with zygomatic muscle neurotization using nerve grafts and end-to-side neurorrhaphies, in a 3-year-old girl diagnosed with bilateral Moebius syndrome who was unable to smile on the left side. After 4 years, the patient presented with full smile restoration on the left side, with right and left independent movements and complete symmetry.